Acute Parkinsonism in a Patient with Spinal Cord Injury: A Case Report - Perrotta, Francesco; Perrini, Marco Paolo; Cantatore, Lea Pia (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Parkinson's disease (PD) is the most common cause of parkinsonism, a clinical syndrome that includes bradykinesia, tremor, and postural instability. Secondary causes of parkinsonism include chronic traumatic encephalopathy. However, clear physiopathologic association between spinal cord injury (SCI) and PD has not been well described yet. We describe a rare/unusual case of a patient with C7–D1 fracture/listhesis who, 12 days after the trauma, developed a progressive cognitive impairment together with mandibular tremor. Seven days after the onset of symptoms, because of the persistence of mandibular tremor and Glasgow Coma Scale (GCS) score of 4, therapy with L-DOPA/benserazide was started, which resulted in gradual reduction of symptoms and complete recovery of consciousness. This could be the first report of PD appearing only 12 days after an SCI in the acute stage. Early differential diagnosis on the first manifestations of this kind of symptoms should be considered in patients with SCI to set up the right therapy essential for improving the outcome and preventing devastating consequences. This might also provide insights into the potential pathophysiologic responses of the brain after primary (immediate) and secondary (delayed) damages.
Keywords: Parkinson's disease; parkinsonism; spinal cord injury